2020
DOI: 10.2147/copd.s275687
|View full text |Cite
|
Sign up to set email alerts
|

<p>Healthcare Service Usage and Costs for Elderly Patients with Obstructive Lung Disease</p>

Abstract: Background The worldwide prevalence of obstructive lung disease (OLD) is increasing, especially among people >65 years old, and nearly three in four adults with OLD have two or more comorbid conditions. This study describes the impact of such comorbidities on the healthcare service usage and related costs in a country with universal health coverage, basing on a large cohort of elderly patients with OLD and employing real-world data. Methods We carried out a retrospectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“… 41 42 Another problem is that they are often unable to properly communicate with their caregivers. 43 Regarding treatment, poor inhaler technique is also an important issue in elderly patients; studies have shown that there is a negative correlation between advancing age and appropriate inhaler technique regardless of inhaler type. 44 Therefore, constant efforts are needed to overcome those fragile aspects of geriatric phenotype and future studies are also needed regarding this topic.…”
Section: Discussionmentioning
confidence: 99%
“… 41 42 Another problem is that they are often unable to properly communicate with their caregivers. 43 Regarding treatment, poor inhaler technique is also an important issue in elderly patients; studies have shown that there is a negative correlation between advancing age and appropriate inhaler technique regardless of inhaler type. 44 Therefore, constant efforts are needed to overcome those fragile aspects of geriatric phenotype and future studies are also needed regarding this topic.…”
Section: Discussionmentioning
confidence: 99%
“…Study results also indicate that a higher number of concomitant therapies and the presence of psychiatric conditions among ET patients were associated with an increased likelihood of receiving [45]. It is well known that patients' expectations as well as patient pressure might result in unnecessary prescriptions, referrals, and investigations [46].…”
Section: Discussionmentioning
confidence: 66%
“…Study results also indicate that a higher number of concomitant therapies and the presence of psychiatric conditions among ET patients were associated with an increased likelihood of receiving treatments. Patients receiving multiple concomitant medications are in fact likely to be affected by different diseases, which in turn demands a great commitment of healthcare services, including diagnostics, hospital services, and physician visits [45]. It is well known that patients' expectations as well as patient pressure might result in unnecessary prescriptions, referrals, and investigations [46].…”
Section: Discussionmentioning
confidence: 99%